Northwest Africa 11024—A heated and dehydrated unique carbonaceous (CM) chondrite. (22nd November 2018) - Ebert, Samuel; Bischoff, Addi; Harries, Dennis; Lentfort, Sarah; Barrat, Jean‐Alix; Pack, Andreas; Gattacceca, Jérôme; Visser, Robbin; Schmid‐Beurmann, Peter; Kimpel, Stephan
Abstract: Based on the high abundance of fine‐grained material and its dark appearance, NWA 11024 was recognized as a CM chondrite, which is also confirmed by oxygen isotope measurements. But contrary to known CM chondrites, the typical phases indicating aqueous alteration (e.g., phyllosilicates, carbonates) are missing. Using multiple analytical techniques, this study reveals the differences and similarities to known CM chondrites and will discuss the possibility that NWA 11024 is the first type 3 CM chondrite. During the investigation, two texturally apparent tochilinite–cronstedtite intergrowths were identified within two thin sections. However, the former phyllosilicates were recrystallized to Fe‐rich olivine during a heating event without changing the textural appearance. A peak temperature of 400–600 °C is estimated, which is not high enough to destroy or recrystallize calcite grains. Thus, calcites were never constituents of the mineral paragenesis. Another remarkable feature of NWA 11024 is the occurrence of unknown clot‐like inclusions (UCLIs) within fine‐grained rims, which are unique in this clarity. Their density and S concentration are significantly higher than of the surrounding fine‐grained rim and UCLIs can be seen as primary objects that were not formed by secondary alteration processes inside the rims. Similarities to chondritic and cometary interplanetary dust particles suggest an ice‐rich first‐generation planetesimal for their origin. In the earliest evolution, NWA 11024 experienced the lowest degree of aqueous alteration of all known CM chondrites and subsequently, a heating event dehydrated the sample. We suggest to classify the meteorite NWA 11024 as the first type 3 CM chondrite similar to the classification of CV3 chondrites (like Allende) that could also have lost their matrix phyllosilicates by thermal dehydration.